Rapid overview of systematic reviews of nocebo effects reported by patients taking placebos in clinical trials - Howick, J; Webster, R; Kirby, N; Hood, K (BioMed Central, 2018)
Background Trial participants in placebo groups report experiencing adverse events (AEs). Existing systematic reviews have not been synthesized, leaving questions about why these events occur as well as their prevalence across different conditions unanswered. Objectives (1) To synthesize the evidence of prevalence of AEs in trial placebo groups across different conditions. (2) To compare AEs in trial placebo groups with AEs reported in untreated groups within a subset of randomized trials. Search methods We searched PubMed for records with the word “nocebo” in the title and “systematic” in any field. We also contacted experts and hand-searched references of included studies. Study eligibility We included any systematic review of randomized trials where nocebo effects were reported. We excluded systematic reviews of non-randomized studies. Participants and interventions We included studies in any disease area. Study appraisal and synthesis methods We appraised the quality of the studies using a shortened version of the Assessment of Multiple Systematic Reviews tool (AMSTAR) tool. We reported medians and interquartile ranges (IQRs) of AEs. Among the trials within the review that included untreated groups, we compared the prevalence of AEs in untreated groups with the prevalence of AEs in placebo groups. Results We identified 20 systematic reviews. These included 1271 randomized trials and 250,726 placebo-treated patients. The median prevalence of AEs in trial placebo groups was 49.1% (IQR 25.7–64.4%). The median rate of dropouts due to AEs was 5% (IQR 2.28–8.4%). Within the 15 of trials that reported AEs in untreated groups, we found that the AE rate in placebo groups (6.51%) was higher than that reported in untreated groups (4.25%). Limitations This study was limited by the quality of included reviews and the small number of trials that included untreated groups. Conclusions and implications of key findings AEs in trial placebo groups are common and cannot be attributed entirely to natural history. Trial methodologies that reduce AEs in placebo groups while satisfying the requirement of informed consent should be developed and implemented.